1966
DOI: 10.1029/jz071i016p03893
|View full text |Cite
|
Sign up to set email alerts
|

The location of the termination area of the equatorial undercurrent in the Gulf of Guinea based on observations during Equalant III

Abstract: During the Equalant III program in the spring of 1964, the Equatorial Undercurrent in the eastern part of the Atlantic Ocean was followed into the inner part of the Gulf of Guinea. The high‐salinity core associated with this current maintained salinities of more than 36.2‰ as far east as the Island of São Tomé. Near 6½°E the subsurface salinity maximum turned to a southeasterly direction, its maximum salinity gradually decreasing in the core. Salinities in excess of 36.2‰ could be observed as close as 150 km o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1973
1973
1992
1992

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…Examples are shown on Figure 24 (Rinkel et al, 1966), Figure 25 and Figure 26 [(a) Le Floch, 1970; Lemasson and Rebert, 1973b]. Additional observations are reported in Hisard and Morli~re (1973), Kolesnikov et al (1971), Morli~re et al (1974), Khanaichenko (1974), Wauthy (1977), Piton, Montel and Gausi (1978), Piton, Besson and Esposito (1978).…”
Section: Eastern Termination Of the Atlantic Eucmentioning
confidence: 59%
See 1 more Smart Citation
“…Examples are shown on Figure 24 (Rinkel et al, 1966), Figure 25 and Figure 26 [(a) Le Floch, 1970; Lemasson and Rebert, 1973b]. Additional observations are reported in Hisard and Morli~re (1973), Kolesnikov et al (1971), Morli~re et al (1974), Khanaichenko (1974), Wauthy (1977), Piton, Montel and Gausi (1978), Piton, Besson and Esposito (1978).…”
Section: Eastern Termination Of the Atlantic Eucmentioning
confidence: 59%
“…Since there are not enough stations to compute any statistically significant mean, we only present on Table 6 these seven instantaneous observations, made close to 6~30'E, 7~30'E and 8~30'E [asterisks (*) on Figure 41]. The 8~30'E profiles are located at the shelf break and were measured from Rinkel et al (1966), and the shear relative to 500 m reported for May 1973 by Morli~re et al (1974) (Figure 31). …”
Section: °-T----""-------l--'im"mentioning
confidence: 99%
“…[1971] for measurements with current meters on unattended moorings). However, the current drogue measurements of Rinkel et al [1966] in the spring of 1964, between 15øW and the coast of Ai•rica, at the depth of the high-salinity core (not necessarily the same as the core ot• the undercurrent), show such large variations that no longitudinal trend is discernible. It is not possible to describe the longitudinal variation of the transport quantitatively, but it is noteworthy that everybody agrees that the transport of the undercurrent is lower in the eastern than in the western Atlantic.…”
Section: Becausementioning
confidence: 99%
“…In the eastern part of the Gulf of Guinea the EUC is split into various branches. One branch can be detected south of the equator, where it approaches the island of Sao Tome (Rinkel et al, 1966) and another one is found in the north. The northern branch feeds into a westward undercurrent along the northern coast of the Gulf of Guinea (LeFloch, 1970).…”
Section: Introductionmentioning
confidence: 97%